2016
DOI: 10.1111/vco.12245
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGFR and PDGFR‐α/‐βin 187 canine nasal carcinomas

Abstract: Radiotherapy represents the standard of care for intranasal carcinomas. Responses to tyrosine kinase inhibitors (TKIs) have been reported but data on expression of target receptor tyrosine kinases (rTKs) is limited. This study characterizes the expression of vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR)-α and PDGFR-β in canine intranasal carcinomas. Histological samples from 187 dogs were retrieved. Immunohistochemistry was performed using commercially ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Canine nasal carcinomas have been shown to express rTKs including KIT and PDGFRα/β, 17 however the lack of phosphorylated target rTKs suggests that toceranib may exert its clinical effects via a different, unidentified mechanism 62 . Seven dogs were treated with toceranib in the previously mentioned study by London et al 28 Of the two dogs that were re‐imaged, 1 had a CR and 1 had SD and an additional 3 dogs experienced improvement in the clinical signs for an overall CB rate of 71.4% 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine nasal carcinomas have been shown to express rTKs including KIT and PDGFRα/β, 17 however the lack of phosphorylated target rTKs suggests that toceranib may exert its clinical effects via a different, unidentified mechanism 62 . Seven dogs were treated with toceranib in the previously mentioned study by London et al 28 Of the two dogs that were re‐imaged, 1 had a CR and 1 had SD and an additional 3 dogs experienced improvement in the clinical signs for an overall CB rate of 71.4% 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies over the last 15 years have demonstrated that a wide array of canine tumours overexpress many of the tyrosine kinases that are targets for these drugs, including KIT, PDGFR and VEGFR. [12][13][14][15][16][17] The majority of these studies focus of toceranib phosphate, rather than masitinib mesylate, likely due to the availability of the former. The aim of this review was to therefore examine the evidence for treatment of non-mast cell tumours in dogs with toceranib phosphate.…”
mentioning
confidence: 99%
“…30,31 Stromal expression of PDGFR-b was present in all samples analyzed in this study whereas previous studies have shown only 60.9% of samples to have stromal staining for PDGFR-b. 13 The development and function of vessels in the TME rely heavily on PDGFR-b and inhibition of this RTK in the TME has been documented in some human solid tumors and may represent an indirect target for toceranib in canine nasal carcinomas. 30,32,33 Interestingly, VEGFR2 and PDGFR-a were not expressed in the tumor stroma in this study; however, PDGFR-a was shown to have nuclear localization.…”
Section: Phosphoprotein Arraysmentioning
confidence: 99%
“…9,12 Several RTK targets of toceranib expressed by canine nasal carcinomas are responsible for angiogenic sprouting and vascular maturation, both defined processes in vasculogenesis and angiogenesis that are imperative for tumor growth. 9,[12][13][14] In one report of 187 dogs with nasal carcinoma, VEGFR was detected in 84.5%, PDGFR-a in 71.1%, and PDGFR-b in 39.6% of tumors by immunohistochemistry. 13 While VEGFR was expressed in the majority of these canine nasal carcinomas, another report showed that 91.7% of epithelial nasal tumors also expressed the VEGF ligand.…”
Section: Chapter 1-introductionmentioning
confidence: 99%
See 1 more Smart Citation